Sonic hedgehog inhibitors prevent colitis-associated cancer via orchestrated mechanisms of IL-6/gp130 inhibition, 15-PGDH induction, Bcl-2 abrogation, and tumorsphere inhibition - Kangwan, Napapan (Oncotarget, 2015)
Sonic hedgehog (SHH) signaling is essential in normal development of the gastrointestinal (GI) tract, whereas aberrantly activated SHH is implicated in GI cancers because it facilitates carcinogenesis by redirecting stem cells. Since colitis-associated cancer (CAC) is associated with inflammatory bowel diseases, in which SHH and IL-6 signaling, inflammation propagation, and cancer stem cell (CSC) activation have been implicated, we hypothesized that SHH inhibitors may prevent CAC by blocking the above SHH-related carcinogenic pathways. In the intestinal epithelial cells IEC-6 and colon cancer cells HCT-116, IL-6 expression and its signaling were assessed with SHH inhibitors and levels of other inflammatory mediators, proliferation, apoptosis, tumorsphere formation, and tumorigenesis were also measured. CAC was induced in C57BL/6 mice by administration of azoxymethane followed by dextran sodium sulfate administration. SHH inhibitors were administered by oral gavage and the mice were sacrificed at 16 weeks. TNF-α–stimulated IEC-6 cells exhibited increased levels of proinflammatory cytokines and enzymes, whereas SHH inhibitors suppressed TNF-α–induced inflammatory signaling, especially IL-6/IL-6R/gp130 signaling. SHH inhibitors significantly induced apoptosis, inhibited cell proliferation, suppressed tumorsphere formation, and reduced stemness factors. In the mouse model, SHH inhibitors significantly reduced tumor incidence and multiplicity, decreased the expression of IL-6, TNF-α, COX-2, STAT3, and NF-κB, and significantly induced apoptosis. In colosphere xenografts, SHH inhibitor significantly suppressed tumorigenesis by inhibiting tumorsphere formation. Taken together, our data suggest that administration of SHH inhibitors could be an effective strategy to prevent colitis-induced colorectal carcinogenesis, mainly by targeting IL-6 signaling, ablating CSCs, and suppressing oncogenic inflammation, achieving chemoquiescence ultimately.